The research on management skills development in higher education - Arroyo-Cañada, Francisco Javier (Journal of Management and Business Education, 2019)
This work provide a review of the research on the development of professional skills in higher education, based on a bibliometric analysis from indexed works in the Social Sciences database at the Web of Science (Clarivate Analytics). The main objective is to analyze the relevance of these studies, in the area of business management, to highlight this research line, which can be found in the Journal of Management and Business Education (JMBE) a relevant source for spread the results to the scientific community.